Effect of inner wall curvature on loss characteristic and flow rectification of curved diffuser - Marzuki, Muhammad Azfar Muqri; Nordin, Normayati; Mohamed Rasidi, Shamsuri (FAZ Publishing, 2022)
A curve diffuser is frequently used in applications such as HVAC, wind tunnel, gas turbine cycle, aircraft engine, etc., as an adapter to join the conduits of different cross-sectional areas or an ejector to decelerate the flow and raise the static pressure before discharging to the atmosphere. The performance of a curve diffuser is measured according to its pressure recovery and flow uniformity. The paper aims to investigate the effect of inner wall curvature numerically and inflow Reynolds number on loss characteristic, and flow rectification Ansys FLUENT was used to simulate the performance of curved diffuser in terms of static pressure coefficient and flow uniformity index by altering the inner wall curvature (Lin/W1 = 1.52, 3.99, 8.99, 13.00 and 25.00) and inflow Reynolds number (Rein= 5.9343 × 104 , 8.1628 × 104 and 1.783 × 105 ). The results show that pressure recovery improved when the inner wall curvature increased from 1.52 to 8.99 for a curved diffuser with an area ratio of 1.6, 2.16, and 4.0. Meanwhile, the increase of inflow Reynolds number caused the flow uniformity to drop at every area ratio of the curved diffuser. The model of the curved diffuser with inner wall curvature of 8.99 and area ratio 4.0 opted as the most optimum producing best pressure recovery up to 0.40 operated at Rein= 5.9343 × 104 . Meanwhile, the model with inner wall curvature of 25.00 and area ratio 4.0, operated at Rein = 5.9343 × 104 , was chosen as the best flow performance with an index of 1.92.